Religion in the Public Sphere : Canadian Case Studies - Beaman, Lori G.; Lefebvre, Solange, 1959- (Book collections on Project MUSE., 2014)
With this edited collection, Solange Lefebvre and Lori G. Beaman bring together a series of case studies of religious groups and practices from all across Canada that re-examine and question the classic distinction between the public and private spheres.